Laser induced fluorescence in nanosecond repetitively pulsed discharges for CO2 conversion. (27th October 2017) - Martini, L M; Gatti, N; Dilecce, G; Scotoni, M; Tosi, P
Abstract: A CO2 nanosecond repetitively pulsed discharge (NRP) is a harsh environment for laser induced fluorescence (LIF) diagnostics. The difficulties arise from it being a strongly collisional system in which the gas composition, pressure and temperature, have quick and strong variations. The relevant diagnostic problems are described and illustrated through the application of LIF to the measurement of the OH radical in three different discharge configurations, with gas mixtures containing CO2 + H2 O. These range from a dielectric barrier NRP with He buffer gas, a less hostile case in which absolute OH density measurement is possible, to an NRP in CO2 +H2 O, where the full set of drawbacks is at work. In the last case, the OH density measurement is not possible with laser pulses and detector time resolution in the ns time scale. Nevertheless, it is shown that with a proper knowledge of the collisional rate constants involved in the LIF process, a collisional energy transfer-LIF methodology is still applicable to deduce the gas composition from the analysis of LIF spectra.